A tumor-targetable NIR probe with photoaffinity crosslinking characteristics for enhanced imaging-guided cancer phototherapy. Issue 9 (13th February 2023) - Sun, Rui; Zhang, Yuqi; Gao, Yinjia; Zhao, Meng; Wang, Anna; Zhu, Jinfeng; Cheng, Xiaju; Shi, Haibin
Abstract : Spatiotemporally manipulating the in situ immobilization of theranostic agents within cancer cells to improve their bioavailability is highly significant yet challenging in tumor diagnosis and treatment. Abstract : Spatiotemporally manipulating the in situ immobilization of theranostic agents within cancer cells to improve their bioavailability is highly significant yet challenging in tumor diagnosis and treatment. Herein, as a proof-of concept, we for the first time report a tumor-targetable near-infrared (NIR) probe DACF with photoaffinity crosslinking characteristics for enhanced tumor imaging and therapeutic applications. This probe possesses great tumor-targeting capability, intensive NIR/photoacoustic (PA) signals, and a predominant photothermal effect, allowing for sensitive imaging and effective photothermal therapy (PTT) of tumors. Most notably, upon 405 nm laser illumination, DACF could be covalently immobilized within tumor cells through a photocrosslinking reaction between photolabile diazirine groups and surrounding biomolecules resulting in enhanced tumor accumulation and prolonged retention simultaneously, which significantly facilitates the imaging and PTT efficacy of tumor in vivo . We therefore believe that our current approach would provide a new insight for achieving precise cancer theranostics.